2021
DOI: 10.1177/1073274821997430
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-PD-1/PD-L1 Immunotherapy for Gastric Esophageal Cancer: A Systematic Review and Meta-Analysis and Literature Review

Abstract: Background: Treatment options for advanced gastric esophageal cancer are quite limited. Chemotherapy is unavoidable at certain stages, and research on targeted therapies has mostly failed. The advent of immunotherapy has brought hope for the treatment of advanced gastric esophageal cancer. The aim of the study was to analyze the safety of anti-PD-1/PD-L1 immunotherapy and the long-term survival of patients who were diagnosed as gastric esophageal cancer and received anti-PD-1/PD-L1 immunotherapy. Method: Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…As the most direct measure of clinical benefit, outcomes of the OS post-treatment with PD-1/PD-L1 inhibitors in trials with esophageal or G/GEJ cancer patients were incongruous. Although previous metaanalyses consistently exhibited improvements in the OS rather than the PFS in esophageal or G/GEJ cancer treatment with PD-1/PD-L1 inhibitor, limitations such as the lack of controlled data or the possibility of known/unknown biases increasing heterogeneity in the analysis might result in less statistically powerful conclusions [6,9]. Furthermore, a previous study included only two studies in the analysis demonstrating improvement of the OS and PFS in the control group, rather than the anti-PD-1 or anti-PD-L1 groups, to treat esophageal or G/GEJ cancer patients [36].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the most direct measure of clinical benefit, outcomes of the OS post-treatment with PD-1/PD-L1 inhibitors in trials with esophageal or G/GEJ cancer patients were incongruous. Although previous metaanalyses consistently exhibited improvements in the OS rather than the PFS in esophageal or G/GEJ cancer treatment with PD-1/PD-L1 inhibitor, limitations such as the lack of controlled data or the possibility of known/unknown biases increasing heterogeneity in the analysis might result in less statistically powerful conclusions [6,9]. Furthermore, a previous study included only two studies in the analysis demonstrating improvement of the OS and PFS in the control group, rather than the anti-PD-1 or anti-PD-L1 groups, to treat esophageal or G/GEJ cancer patients [36].…”
Section: Discussionmentioning
confidence: 96%
“…Pathophysiologically, gastrointestinal tumors are traditionally considered nonimmune-related malignancies. However, current reports have provided a new direction in the treatment by demonstrating the effectiveness of blocking specific immunosuppressive substances, such as programmed death receiver 1/programmed death ligand 1 (PD-1/PD-L1) [6]. Current studies have indicated that the number of tumor-infiltrating lymphocytes is related to tumor prognosis [7] and the correlation between malignant tumors and immune cells such as T cells.…”
Section: Introductionmentioning
confidence: 99%
“…79 The programmed death-ligand 1 (PD-L1)/programmed death-1 (PD-1) checkpoint pathway may be important for the prediction of disease-free survival, overall survival, cancer relapse, treatment response rate and susceptibility, metastasis, lymph node invasion, tumor stage, and incidence of post-therapeutic adverse effects in patients with EC. 8082 The modulation of this pathway can inhibit immunosuppression, tumorigenicity, self-renewal, immune escape, proliferation, metastasis, EMT, and treatment resistance of EC cells and tumors, and can enhance the antitumor immune response and survival in EC. 8082 The TNF pathway determines the treatment sensitivity, viability, and growth of EC cells and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated survival advantages with monoclonal antibodies targeting PD-1/PD-L1 ( e.g. , pembrolizumab, nivolumab) in patients with advanced gastric esophageal cancer[ 26 ].…”
Section: Future Directionsmentioning
confidence: 99%